Recurrent hyperammonemic encephalopathy in a breast cancer patient receiving capecitabine therapy: a case report and literature review - Mu, Yuling; Li, Qing; Kong, Jilin; Zhao, Yuyao (Frontiers in Pharmacology, 2026)
Capecitabine-induced hyperammonemic encephalopathy represents a rare adverse event that can complicate clinical diagnosis. To accurately diagnose this condition, clinicians should consider a combination of factors, including the patient’s history of capecitabine use, clinical manifestations of altered mental status accompanied by hyperammonemia, and the exclusion of alternative causes for the altered level of consciousness. We report a case of a female patient with breast cancer who developed hyperammonemic encephalopathy during her first cycle of a capecitabine-containing chemotherapy regimen, with a peak plasma ammonia level of 191.4 μmol/L. Discontinuation of capecitabine, together with hemoperfusion, and other ammonia-lowering therapies, led to the normalization of ammonia levels, restoration of consciousness, and recovery of laboratory parameters and vital signs. The patient was subsequently switched to S-1, which she tolerated well for 14 months without significant adverse effects. However, upon reintroduction of a capecitabine-containing regimen due to disease progression, hyperammonemic encephalopathy recurred, with a peak ammonia level of 333.6 μmol/L. After cessation of capecitabine and initiation of plasmapheresis and other ammonia-reducing treatments, her ammonia levels normalized, consciousness was restored, and all laboratory and clinical parameters returned to normal. This case underscores the necessity of maintaining a high index of suspicion for rare adverse reactions, even in patients with complex medical histories. While it is typically more pragmatic to prioritize common etiologies initially, clinicians must remain open-minded in their differential diagnosis when conventional explanations fail to account for the clinical presentation.